The background of the odal rights: an archaeological discussion - Zachrisson, Torun (Danish Journal of Archaeology, 2017)
The age and origin of the odal rights known from medieval times in Sweden and Norway are debated. Archaeologists tend to view them as old and a part of the pre-Christian society, whereas historians and legal historians view them as established after Christianity was introduced, mirroring canonical laws. In Viking Age runic inscriptions from the eleventh century in the lake Mälaren valley in Sweden, from late tenth to eleventh century in south-western Norway, the term odal, inherited family land occurs together with other expressions concerning landed property. Furthermore, two runestones in Småland and Hälsingland in Sweden, c. 650 km apart, each enumerate five earlier ancestors in a male lineage, the sponsor himself being the sixth generation. As these runic inscriptions were made in different parts of Scandinavia during the late tenth and eleventh century, this indicates that the term and concept odal was widespread already before the canonic laws of the early medieval period were introduced, and quite possibly belongs to an older inheritance structure. The aim of this article is a renewed discussion focussing on the runological sources where the term and concept odal can be found in the Viking Age Scandinavian society (c. 750–1050 CE), but also early medieval written sources. Thereafter, archaeological sources from the Late Iron Age are addressed (c. 550–1050 CE).